Boosting Reaction Homogeneity in High‐Energy Lithium‐Ion Battery Cathode Materials. Issue 39 (20th August 2020) - Cha, Hyungyeon; Kim, Junhyeok; Lee, Hyomyung; Kim, Namhyung; Hwang, Jaeseong; Sung, Jaekyung; Yoon, Moonsu; Kim, Kyungho; Cho, Jaephil
Abstract: Conventional nickel‐rich cathode materials suffer from reaction heterogeneity during electrochemical cycling particularly at high temperature, because of their polycrystalline properties and secondary particle morphology. Despite intensive research on the morphological evolution of polycrystalline nickel‐rich materials, its practical investigation at the electrode and cell levels is still rarely discussed. Herein, an intrinsic limitation of polycrystalline nickel‐rich cathode materials in high‐energy full‐cells is discovered under industrial electrode‐fabrication conditions. Owing to their highly unstable chemo‐mechanical properties, even after the first cycle, nickel‐rich materials are degraded in the longitudinal direction of the high‐energy electrode. This inhomogeneous degradation behavior of nickel‐rich materials at the electrode level originates from the overutilization of active materials on the surface side, causing a severe non‐uniform potential distribution during long‐term cycling. In addition, this phenomenon continuously lowers the reversibility of lithium ions. Consequently, considering the degradation of polycrystalline nickel‐rich materials, this study suggests the adoption of a robust single‐crystalline LiNi0.8 Co0.1 Mn0.1 O2 as a feasible alternative, to effectively suppress the localized overutilization of active materials. Such an adoption can stabilize the electrochemical performance of high‐energy lithium‐ion cells, in which superior capacity retention above ≈80% after 1000 cycles at 45 °C is demonstrated. Abstract : Boosting reaction homogeneity in high‐energy lithium‐ion battery cathode materials is important to stabilize their electrochemical performance. However, conventional nickel‐rich materials suffer from morphological collapse which deteriorates the electrode integrity with heterogeneous reaction behavior. To mitigate these issues, mechanically robust single‐crystalline nickel‐rich particles are suggested. They perfectly maintain their chemo‐mechanical properties during the harsh electrochemical testing condition.